2019
DOI: 10.18203/2349-3291.ijcp20192017
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of retinopathy of prematurity in Goa, India: a report from tertiary care centre

Abstract: Background: To report the incidence and risk factors leading to the development of retinopathy of prematurity (ROP) from a tertiary care center in the western Indian state of Goa, India.Methods: This was a prospective observational study carried out in a level II neonatal intensive care unit (NICU) for a period of 18 months. Babies born at < 34 weeks’ gestation and having a birth weight of <1500gm were screened for ROP and laser photocoagulation was done for those who developed threshold ROP. Group diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
3
3
3
Order By: Relevance
“…A significant relationship between birth weight and ROP was also confirmed by multivariate logistic regression analysis by which birth weight less than 1725 g was associated with a 4.5-fold increase in the risk of ROP (OR = 4.522, 95% CI: 2.677-7.637, P <0.001). This finding is consistent with many previous studies (4,(11)(12)(13)16,17,19).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…A significant relationship between birth weight and ROP was also confirmed by multivariate logistic regression analysis by which birth weight less than 1725 g was associated with a 4.5-fold increase in the risk of ROP (OR = 4.522, 95% CI: 2.677-7.637, P <0.001). This finding is consistent with many previous studies (4,(11)(12)(13)16,17,19).…”
Section: Discussionsupporting
confidence: 94%
“…ROP is a multifactorial disease in which low gestational age at birth has been suggested in several studies as an important risk factor for this disease. In studies in India, Pakistan, Mexico, Portugal, Oman, and Isfahan, the gestational age of neonates with retinopathy at birth was significantly lower than that of nonpatients (4,11,13,14,16,17), which are in accordance with our findings. In a study by Ludwig et al (2017) in the United States, multivariate regression analysis showed that gestational age was an independent predictor of ROP (12), which is similar to the present study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…ROP is a multifactorial disease in which low gestational age at birth has been suggested in several studies as an important risk factor for this disease. In studies in India, Pakistan, Mexico, Portugal, Oman, and Isfahan, the gestational age of neonates with retinopathy at birth was significantly lower than that of non-patients, 4,11,13,14,16,17 which are in accordance with our findings. In a study by Ludwig et al (2017) in the United States, multivariate regression analysis showed that gestational age was an independent predictor of ROP, 12 which is similar to the present study.…”
Section: Discussionsupporting
confidence: 91%